Effect of Learning Environment on Academic Performance of Pupils and Students in Kagango Division Sheema Municipality. - Andonzire, Steve James (Kabale University, 2024)
This study was about assessing the effect of the learning environment on the academic performance of pupils and students in Kagango Division Sheema Municipality. lt was guided by specific objectives which were to describe the factors that cause students' decline in academic performance, to find out the relationship between school environment and academic performance; Pupils and Students in Kagango Division Sheema Municipality and to suggest possible solutions to the effect of learning environment on academic performance of pupils in pre¬primary, primary and secondary schools. The researcher used a descriptive cross-sectional survey where data was collected across the population at one point in time because it ought to describe the issues, the study was conducted in four selected schools in the Division and these were Kihunda primary School and Kihunda parents' secondary school. Rwabutura primary school and Itendero secondary school. The study sampling was cloned on ~l I lead teachers, 30 students, 8 Teachers: and 8 parents from Kagango Division which were both male and female. Both a questionnaire and interview guide were used to collect data and findings indicated that more males participated in the study than females. Respondents who were below 20 years old participated more than the rest of and respondents. The study concluded that more respondents were single than the rest. Also concerning the education background, it was concluded that many respondents were secondary school students and the less number of respondents had attained diplomas and degrees as their qualifications like parents and head teachers. The study concluded that factors that cause students' decline in performance in secondary schools are poverty, domestic violence, Limited evaluation, peer pressure, and Absenteeism. Teasing and bullying and 18% suggested alcoholism. The study also shows the relationship between school environment and students' academic performance to be school environment, giving tests and coursework, strikes and demonstrations, Poor student-teacher relationships, guidance and counseling, poor class control, and Poor methods of teaching. Finally, the study concluded that t-, classes that can be taken to improve performance in secondary schools as Giving rewards to the best-performing students, Government Involvement in Education, Offering support to the suffering students, providing career guidance in schools, Providing Alternative Sources of power and Encouraging Substitutes and finally the study recommended that the government to support students, especially through organizing seminars to equip students with the necessary knowledge from different angles, establish and implement a new curriculum for all schools in way to be more of practical than theory, school management committees of the selected schools to always assess the performance of teachers in teaching through tasking them to produce timetable and lesson plans prioritize investment in education and develops policies to improve the financing of the education in such way as to provide adequate educational facilities for all schools.